Particle physics and cosmology: the fabric of spacetime : Ecole d'ete de Physique des Houches, session LXXXVI, 31 July - 25 August 2006 ; Ecole thematique du CNRS /: Ecole d'ete de Physique des Houches, session LXXXVI, 31 July - 25 August 2006 ; Ecole thematique du CNRS. (2007) - Unknown
No abstract available